2009
DOI: 10.1111/j.1540-8175.2008.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Myocardial Functional Alterations in Patients with Obstructive Sleep Apnea Syndrome

Abstract: Patients with OSAS display a regional pattern of right ventricular dysfunction correlated with the severity of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 21 publications
2
32
1
1
Order By: Relevance
“…These results are consistent with a previous large cross-sectional study by Niroumand et al, who found no significant difference in the E/A ratio between OSAS and non-OSAS patients [15]. However, in several other studies, associations were reported between OSAS severity and E/A ratio [35,36], A peak wave [36] or LA volume [37], with reversibility after a few months of CPAP treatment [33,37,38]. Furthermore, AHI was significantly correlated Left ventricular diastolic function in obstructive sleep apnoea syndrome 9 with LAA, which is a surrogate for diastolic function.…”
Section: Left Ventricular Diastolic Functionsupporting
confidence: 94%
“…These results are consistent with a previous large cross-sectional study by Niroumand et al, who found no significant difference in the E/A ratio between OSAS and non-OSAS patients [15]. However, in several other studies, associations were reported between OSAS severity and E/A ratio [35,36], A peak wave [36] or LA volume [37], with reversibility after a few months of CPAP treatment [33,37,38]. Furthermore, AHI was significantly correlated Left ventricular diastolic function in obstructive sleep apnoea syndrome 9 with LAA, which is a surrogate for diastolic function.…”
Section: Left Ventricular Diastolic Functionsupporting
confidence: 94%
“…LV systolic longutidinal dysfunctions of myocardium can be evaluated quantitatively by TDI method. Previous TDI studies have showed that OSA accompanied by sleep-induced LV systolic longutidinal dysfunction (34)(35)(36). TDI is more sensitive than EF in the detection of subtle changes in the LV contractile function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have shown various impaired LV diastolic function markers in patients with OSAS compared with in controls: enlarged left atrial size [46,[78][79][80], prolonged isovolumic relaxation time (IVRT) [46,57,78,81], altered E/A ratio [46,78,79,[81][82][83][84], lower early diastolic mitral annular velocity (e ) [79,82,83,85,86] and increased E/e ratio [43,78,87] (Fig. 3).…”
Section: Diastolic Dysfunction In Osasmentioning
confidence: 96%